A study on the allelopathic tolerance of garden pea varieties to Sorghum halepense (L.) Pers. extracts - Georgieva, Natalia; Kosev, Valentin; Kalapchieva, Slavka (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2021)
The present research study identified garden pea varieties with pronounced tolerance to the allelopatic action of Sorghum halepense. Nine varieties were selected to study the effects of shoot and root weed biomass, applied in three extract concentrations (1, 5 and 10%), on seed germination and initial germ growth. A variance analysis of data revealed significant influence (p <0.05) of three studied factors (variety, type and concentration of extracts) on the investigated parameters. Statistically insignificant was only the influence of extract type (root/aboveground biomass) on seed germination. Based on absolute values of the allelopathic indicator RI, which determines the degree of allelopathic inhibition in terms of germination, germ length and weight in different varieties, the variation was as follows: from -0.30 to -0.04, from -1.31 to -2.96 and from -0.47 to 0.02. The total effect of allelopathic action of S. halepense on all studied parameters, presented as a GGE-biplot analysis, defined Pulpudeva and Puldin varieties as exhibiting higher tolerance, in contrast to Denitsa and Vyatovo, which were sensitive. Ran I, Mira, Musala and Vechernitsa occupied an intermediate position. Cultivation of allelopathic tolerant varieties is a promising addition to the current weed control strategy, especially in organic production.